Development of reporter genes for in vivo imaging of Staphylococcus aureus - Lamb, Rochelle Marie (2010)
S. aureus is an opportunistic pathogen with an extensive host range, and is the etiologic agent of a wide variety of human diseases, with the ability to promote disease in most human tissues. A repertoire of virulence factors expressed during colonization and infection all contribute to the success of S. aureus as a pathogen. S. aureus is not classically considered as an intracellular pathogen, yet accumulating scientific evidence has demonstrated that this organism has intracellular survival strategies, with the ability to become internalised by, and persist within, a wide range of non-professional eukaryotic phagocytes. This phenomenon has been shown to be linked to the expression of genes under the regulation of the S. aureus quorum sensing system, agr. Specifically, S. aureus has been shown to breach the host-membrane bound endosome within which it is situated upon internalisation, a process which has been hypothesised to rely upon a switch in gene expression due to the accumulation of the agr signalling peptide within the endosome.